Halide-Mediated Modification of Magnetism and Electronic Structure of α-Co(II) Hydroxides: Synthesis, Characterization, and DFT+U Simulations - Oestreicher, Víctor Santiago Jesús (2019)
The present study introduces a comprehensive exploration in terms of physicochemical characterization and calculations based on density functional theory with Hubbard's correction (DFT+U) of the whole family of α-Co(II) hydroxyhalide (F, Cl, Br, I). These samples were synthesized at room temperature by employing a one-pot approach based on the epoxide route. A thorough characterization (powder X-ray diffraction, X-ray photoelectron spectroscopy, thermogravimetric analysis/mass spectroscopy, and magnetic and conductivity measurements) corroborated by simulation is presented that analyzes the structural, magnetic, and electronic aspects. Beyond the inherent tendency of intercalated anions to modify the interlayer distance, the halide's nature has a marked effect on several aspects. Such as the modulation of the CoOh to CoTd ratio, as well as the inherent tendency towards dehydration and irreversible decomposition. Whereas the magnetic behavior is strongly correlated with the CoTd amount reflected in the presence of glassy behavior with high magnetic disorder, the electrical properties depend mainly on the nature of the halide. The computed electronic structures suggest that the CoTd molar fraction exerts a minor effect on the inherent conductivity of the phases. However, the band gap of the solid turns out to be significantly dependent on the nature of the incorporated halide, governed by ligand to metal charge transfer, which minimizes the gap as the anionic radius becomes larger. Conductivity measurements of pressed pellets confirm this trend. To the best of our knowledge, this is the first report on the magnetic and electrical properties of α-Co(II) hydroxyhalides validated with in silico descriptions, opening the gate for the rational design of layered hydroxylated phases with tunable electrical, optical, and magnetic properties.